NILAI-NILAI BUDAYA PADA KESENIAN NANDONG DI KABUPATEN INDRAGIRI HULU - Ficki Rhanidia Fonda; Syafrial Syafrial; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to find out the cultural values available in Nandong in Indragiri Hulu Regency. The type of research used is qualitative with descriptive method. Technique of writing data in this research is interview technique, recording, process and direct information arts nandong Indragiri Hulu Regency. The data collected were obtained from 3 informants. The data collected were analyzed using Milles and Huberman theory with several stages: data reduction, data presentation, and conclusion reduction. Judging from the average number of scores, the authors derived results from cultural values on data in Indragiri Hulu District found data with problems from the data found. The problem of the essence of the human work is found in three data. The problem of the right of human proximity to time space was found to be four data. The problem of the nature of human relationships with the natural surroundings only found one data. The problem of the nature of human relationships with each other will find as many as eleven data.Keywords: Art, nandong, cultural values.